Effectiveness of Health Promotion Through Audiovisual Media and Lecture Methods on the Level of Knowledge in Elementary School Children About TB Disease - Trifitriana, Monica; Fadilah, Mariatul; Mulawarman, Rido (Fakultas Kedokteran Universitas Pelita Harapan, 2019)
Introduction : Indonesia is the number two country for TB incidence in the world. To reduce the morbidity and death rate of tuberculosis cases, WHO issued an END-TB Strategy program that has 3 pillars. Pillar number 2 on the importance of cooperation with government, private stakeholders, and community for the prevention of TB disease, one of them in the form of health promotion. The application of speech methods and audiovisual media in conveying information has some differences in the process and achievement of students' level of understanding. This study aims to compare the effectiveness of the use lecture methods and audiovisual media in conveying information.Method : A total of 136 research subjects were 6th graders at Public Elementary School 205 Palembang and Private Elementary School YWKA Palembang divided into 2 groups for each elementary school. Each elementary school were subdivided into two groups, namely the audiovisual media group and the lecture method group. This study used quasi experimental design with nonequivalent pretest-posttest technique.Result : After the intervention, the level of understanding for the audiovisual media group was 87.90% while for the lecture method was 83.00% (effective when> 75%) with a value of p <0.05. Conclusion: the delivery of information on TB disease in grade 6 students assessed in two schools, both public and private, using audiovisual media and lecture methods were both equally effective, but the effectiveness of the audiovisual media was higher than the lecture method so that audiovisual media is considered better than lecture methods.